Calculus complete introduction : a complete introduction - Neill, Hugh, ....- (London : Teach Yourself, 2013)
Calculus: A Complete Introduction is the most comprehensive yet easy-to-use introduction to using calculus. Written by a leading expert, this book will help you if you are studying for an important exam or essay, or if you simply want to improve your knowledge. The book covers all areas of calculus, including functions, gradients, rates of change, differentiation, exponential and logarithmic functions and integration. Everything you will need to know is here in one book. Each chapter includes not only an explanation of the knowledge and skills you need, but also worked examples and test questions.
Previously published as Teach yourself calculus and Understand calculus: teach yourself
Based on original material by Paul Abbott
Keywords: Calculus -- Textbooks; Differentiaalrekening; Integraalrekening